2015
DOI: 10.3727/096368913x675719
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Human Corneal Endothelial Cells: A Novel Dual Media Approach

Abstract: Corneal endothelium-associated corneal blindness is the most common indication for corneal transplantation. Restorative corneal transplant surgery is the only option to reverse the blindness, but a global shortage of donor material remains an issue. There are immense clinical interests in the development of alternative treatment strategies to alleviate current reliance on donor materials. For such endeavors, ex vivo propagation of human corneal endothelial cells (hCECs) is required, but current methodology lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
186
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(201 citation statements)
references
References 64 publications
5
186
0
2
Order By: Relevance
“…Such reversibility has also been observed in primary human corneal cells 30, indicating that the immortalized HMGECs share characteristics of primary cells. Indeed, we have previously found that many of the genetic responses of immortalized HMGECs are the same as those of primary HMGECs 18.…”
Section: Discussionmentioning
confidence: 54%
“…Such reversibility has also been observed in primary human corneal cells 30, indicating that the immortalized HMGECs share characteristics of primary cells. Indeed, we have previously found that many of the genetic responses of immortalized HMGECs are the same as those of primary HMGECs 18.…”
Section: Discussionmentioning
confidence: 54%
“…In particular, significant progress has been made in the field of corneal endothelial cell engineering iovs.arvojournals.org j ISSN: 1552-5783 over the last decade. 5 The successful development of in vitro techniques to stimulate proliferation and migration of cultured CECs 17,18 has led to attempts to translate these results clinically. 19 Fuchs' endothelial dystrophy (FED) is a primary cornea endotheliopathy characterized by guttate excrescences on the DM, 20 accompanied by the presence of dysfunctional CECs.…”
mentioning
confidence: 99%
“…The cells also expressed endothelium-associated markers. Using this method, 7-day exposure to maintenance medium showed differential gene expression associated with cell proliferation and wound healing, which eventually confirmed that this is a reproducible and consistent method for the culture of HCECs [34].…”
Section: Cultivation Of the Primary Human Donor Corneal Cells Using Amentioning
confidence: 51%